Thinking Time in Healthcare: Popular Promise, Limited Evidence — A Review of Online Discourse - Kaya Bhandari; Mark Phillips; Goran Calic; Alex Thabane; Mohit Bhandari (International Multispeciality Journal of Health, 2026)
In healthcare, the importance of taking time to 'think deeply' about a challenge or an opportunity is especially important because decisions often require healthcare leaders to integrate uncertainty, competing priorities, patient values, and the best available evidence. Deliberate pauses for reflection, often called "thinking time," are widely promoted as a way to enhance creativity and productivity, yet most public guidance comes from blogs and online media rather than scientific research. This review examined how thinking time is portrayed in popular online discourse, with the aims of exploring how it is defined, what benefits and outcomes are emphasized, what daily durations are recommended, and what strategies are proposed for its implementation. We searched Google (2015-2025) for English-language blogs and articles explicitly discussing thinking time and extracted data on authorship, publication type, use of references, recommended durations, benefits, outcomes, and implementation strategies. One hundred articles were included. Most were published in the past five years, written by individuals with post-secondary education, and presented as personal blogs. Seventy percent provided no references, and few cited scientific sources. Benefits were most often linked to creativity and innovation. Recommended amounts were heterogeneous and were most often expressed weekly (commonly 30-120 minutes per week, or approximately 4-15 minutes each day); where daily figures were given they ranged from a few minutes to several hours. Strategies included time blocking, reducing distractions, journaling, reflection, collaboration, and walking. Online discourse strongly endorses thinking time despite limited scientific evidence, highlighting the need for rigorous research to test optimal protocols and outcomes.